1970
DOI: 10.1017/s0021859600022826
|View full text |Cite
|
Sign up to set email alerts
|

The effect on nitrogen utilization in the sow of variation in dietary protein concentration and pattern of feeding in pregnancy

Abstract: In a factorial experiment, two protein concentrations and three patterns of feeding were administered to eighteen Large White x Wessex sows (three per treatment) in their second pregnancy. Treatments were repeated in their third pregnancy, when balance trials were conducted. The high protein diet (HP) (19-5% crude protein) contained 15 % white-fish meal. The low protein diet (LP) (10-5 % crude protein) contained protein of vegetable origin only. The pattern treatments involved intakes of 1-8 kg (L) 2-7 kg (C) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1971
1971
1992
1992

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…The linear increase in N retention with increasing dietary protein is similar to that reported by Miller et al (1969) and Jones and Maxwell (1974) in early gestation and by Jones and Maxwell (1982) throughout gestation. The energy effect is consistent with the findings of Pike (1970), who observed an increase in N retention with increasing energy levels in gestating swine. In a review by Munro (1964), studies with adult rats, dogs and humans showed that within limits, additional energy resuited in an increased N retention of 2 to 4 mg of N/kcal of energy.…”
Section: Resultssupporting
confidence: 91%
“…The linear increase in N retention with increasing dietary protein is similar to that reported by Miller et al (1969) and Jones and Maxwell (1974) in early gestation and by Jones and Maxwell (1982) throughout gestation. The energy effect is consistent with the findings of Pike (1970), who observed an increase in N retention with increasing energy levels in gestating swine. In a review by Munro (1964), studies with adult rats, dogs and humans showed that within limits, additional energy resuited in an increased N retention of 2 to 4 mg of N/kcal of energy.…”
Section: Resultssupporting
confidence: 91%
“…Nevertheless this rate of intake would seem to have met the minimum protein and lysine requirements in our experiment for maximum litter productivity and the evidence of Frobish, Speer & Hays (1966) showed that as little as 182 g protein per day did not depress the number of live pigs farrowed. Pike (1970) observed no change in litter size when a diet containing white fish meal and providing 526 g protein replaced a vegetable protein diet providing 284 g protein. The negative response to additional protein may have been partly the consequence of the low gestation feeding scale in treatment hL-hH.…”
Section: Discussionmentioning
confidence: 87%